The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1074/jbc.a109.040964
|View full text |Cite
|
Sign up to set email alerts
|

Dual activities of odorants on olfactory and nuclear hormone receptors.

Abstract: On page 30551, Table 1, first column, the experimentally determined values of EC 50 of ER activation for MC, Polysantol, Javanol, and androstenol have been presented with the wrong concentration (mM). The correct concentration is M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Studies focusing on other GPCRs, like rhodopsin and the AT1 angiotensin receptor, have shown that loss of glycosylation may lead to a decreased receptor function or stability. , These findings indicate that the production of ORs in mammalian cells might be crucial for functional expression and purification. Apart from these obvious advantages, mammalian expression systems also offer the possibility of probing OR function directly in the same heterologous cell type used for protein production. ,,, This is not possible in bacterial or insect cell expression systems or in the recently emerging cell-free OR production systems. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies focusing on other GPCRs, like rhodopsin and the AT1 angiotensin receptor, have shown that loss of glycosylation may lead to a decreased receptor function or stability. , These findings indicate that the production of ORs in mammalian cells might be crucial for functional expression and purification. Apart from these obvious advantages, mammalian expression systems also offer the possibility of probing OR function directly in the same heterologous cell type used for protein production. ,,, This is not possible in bacterial or insect cell expression systems or in the recently emerging cell-free OR production systems. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no high-resolution three-dimensional (3D) structure of an OR has been determined, in contrast to those of other mammalian GPCRs. Consequently, a reliable structural basis of OR’s ligand recognition is unknown. Therefore, only models of ligand binding sites of ORs have been proposed on the basis of sequence comparisons between ORs, by functional studies of mutant OR proteins, and by comparisons with known 3D structures of other GPCRs. Finally, quantitative thermodynamic and kinetic constants for interactions between ORs and their activating ligands or their downstream signaling proteins are totally missing. Hence, methods for the efficient production of ORs in their biologically active form are of crucial importance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of some ORs is reported to be controlled by odorants which are dually active; OR2A1 is known to be regulated by sandalwood compounds which initiate neuronal signaling as well as hormonal transcriptional control of speci c genes. [45,44]. OR51E2/PSGR, a marker of prostate cancer and OR7D4 can be activated by androstenone [46][47][48][49][50], also, OR51E1 is reported to associate with gastrointestinal neuroendocrine carcinomas [51], It can be activated by steroid hormones [13].…”
Section: Discussionmentioning
confidence: 99%